Accounting and Analytical Aspects of the Budgeting Organization at the Ukrainian Enterprises - PYLYPENKOО. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The economic crisis in the management system causes the impossibility of economic growth and necessitates the study of opportunities to improve accounting and analytical support of budgeting to promote economic development of the Ukrainian enterprise. The aim of the study is to determine the areas of accounting and analytical support for the organization of budgeting in enterprises in modern business conditions, which are focused on the provisions of IFRS. Taking into account the typical problems of the budgeting process at the present stage allowed to determine the need for further development of this management technology based on accounting. It is taken into account that in the practice of management of Ukrainian enterprises there is different experience in implementing the budgeting system and a set of practical problems that hinder its effectiveness. This allowed to determine the list of additional requirements for accounting and analytical support of budgeting, in particular through the introduction of clear regulations and adjustment of budgeting methods, because the readiness for unpredictable developments significantly affects the future of the enterprise. The need for proper accounting and analytical support of budgeting based on the formation of appropriate requirements for computerization of the accounting process, automatic generation of information on the results of budget reviews and changes in budgets, data on the feasibility of meeting short-term goals (profits) or long-term innovation objectives reporting with relevant analytical indicators for budgeting, formation of data on client and intellectual capital in the company’s reporting, organization of document flow and limited access to budget indicators and results of their implementation, choice of methods of analysis of budget execution and achieved indicators, proper distribution of responsibilities of accounting staff and analysts. The formulated scheme of accounting and analytical support of budgeting on the basis of the accounting policy of the enterprise takes into account all the necessary elements of budgeting for analytical data processing and determination of budget indicators.